(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
As the primary language of Afroasiatic macrosemy, Arabic holds a unique position in the field of linguistics. In order to solve the issue of language emergence in general, it is crucial to take into account the key phases in this language’s development as well as its distinctive qualities